Diseño y construcción de dos tableros eléctrico – electrónico para la comunicación a larga distancia utilizando tecnología GSM para el control automático del nivel de un tanque de agua para una junta barrial de agua potable. - Santo Guanoluisa, Milton Armando (2023)
This research project focuses on the implementation of two boards for automatic level control in a water tank, the need for implementation has been seen due to the distance that exists between the pumping system and the collection tank, which is about a kilometer without line of sight. Currently, the supply of drinking water is carried out with a manual control, which results in a problem in terms of the continuous shortage of water, the high cost of electricity billing, and the operator's monthly salary.